i'm extremely stuck on this problem.
it's y=x^{2}+x.
i know the first step is switching y and x to get x=y^{2}+y, but i don't know what to do afterwards to inverse it, and i am supposed to use the quardatic equation?
please help, thanks!
xkiwibird wrote:i'm extremely stuck on this problem.
it's y=x^{2}+x.
i know the first step is switching y and x to get x=y^{2}+y, but i don't know what to do afterwards to inverse it, and i am supposed to use the quardatic equation?
please help, thanks!
xkiwibird wrote:it's y=x^{2}+x.
... i don't know what to do afterwards to inverse it, and i am supposed to use the quardatic equation?